When Florence met Freud: interaction and intersection between psychoanalysis and nursing. - Ramsey, Sarah M. (Psychoanalytic Psychotherapy, 2024)
A theoretical paper which considers the previous multiple attempts by nursing to engage with and usefully apply the theories of psychoanalysis to varying aspects of the nursing role. References to psychoanalysis within the nursing literature of the last century are reviewed and the legitimacy of the use of psychoanalytic theory 'outside the clinic' explored with reference to general hospital nursing in the UK's National Health Service. Themes explored include unconscious motivation behind nursing as a career choice, with associated risks of stress and burnout when the unconscious drive to heal is thwarted. Psychoanalytic consideration of nurse-patient relationships provides insight into the patient experience on hospital wards, whilst exploration of other aspects of the nursing role was found to be limited. From a wider perspective, psychoanalysis offers nursing an insight into societal changes impacting the profession. The systems and processes of the healthcare institution have also been explored, particularly in relation to containment of anxiety, though limited practical impact has resulted from the psychoanalytic insight encountered in the literature. The limited engagement between psychoanalysis and general nursing is considered from both a psychoanalytic and nursing perspective; ongoing potentiality for enriching dialogue between the disciplines is established and potential barriers explored.